THU0172 Adverse Events to Biologic Agents in Elderly Patients with Rheumatoid Arthritis: Cohort with 13 Years of Follow-up. (9th June 2015) - Rosales Rosado, Z.; Freites Núñez, D.; Gόmez Gόmez, A.; Arietti Lόpez, L.; Macarrόn Pérez, P.; Leal Pozuelo, J.M.; Jover Jover, J. Ά.; Abásolo Alcázar, L.
Abstract : Background: After more than a decade using biological agents (BA), is widely known their efficacy in the treatment of Rheumatoid Arthritis (RA) and their relationship with Adverse Events (AE). We know that drugs metabolism changes with age and, thus, the AE but we have no concrete information about AE with BA in these patients in real life. Objectives: To describe the incidence and characteristics of moderate and severe AE to BA in a cohort of elderly patients with RA. Methods: We conducted a retrospective longitudinal observational study from January 1st 2000 to November 18th 2013. Subjects: RA patients followed in the out-patient clinic at Hospital Clinico San Carlos, who started treatment with BA when they were older than 65 years in the study period. Primary endpoint: development of an AE (moderate: suspension of the drug regardless of the impact; severe: suspension and hospitalization or death) to BA. Secondary endpoints: a) sociodemographic (age, sex); c) clinical (disease duration, type of BA (etanercept (ETN), golimumab (GOLI), certolizumab (CTZ), infliximab (IFX) and adalimumab (ADA); other biological: rituximab (RTX), abatacept (ABATA), tozilizumab (TZL)) Analysis: description of sociodemographic and clinical characteristics of patients included and causes of AE by frequency distribution, and the mean and standard deviation. The incidence of AE using survival techniques, expressing the incidence in 100 patients * year with their respective 95% confidence interval (95% CI). Results: 146 elderly patients with RA were included in the study, which began 286 different courses of treatment with BA; follow-up was 604.5 patients * year. Of these, 78% were women with a mean age at diagnosis of 66.5±7 years and a mean time to first BA of 6±5 years. The most frequently used drug was ADA (27.3%), followed by IFX (22.4%), ETN (21.3%) and RTX (19.2%). 111 AE were recorded with a BA survival in the first year of 71% which decreased over time, being 35% at 5 years. The rate of AE was 18.4 (95% CI 15.2 to 22.1), in Table 1 we present AE incidence by BA. The most common cause of AE was infections (50.5%) with an incidence of 9.3 (95% CI 7.1 to 12). 56% were severe AEs with an incidence of 10.3 (95% CI 8 to 13.2). The main cause of serious AE was infections (51.6%) followed by congestive heart failure. 16 deaths were registered with a mortality rate of 2.7%. Conclusions: After 5 years of treatment, two thirds of the patients over 65 years have discontinuated BA due to AE. The AE rate is estimated at 18.4 per 100 patient * year in general and 10.3 in severe AE, being infections the most common cause in both. IFX was the drug with the highest incidence of AE. The mortality rate in our study was 2.7%. This study contributes to increase the knowledge of the AE to BA in the long term in RA patients over 65 years on real life conditions. Disclosure of Interest: None declared